Effectiveness of Giemsa and Modified Trypan Blue-GiemsaStaining for the Assessment of Acrosome Integrity in Bull andBuck semen - Ruthrakumar , Ravichandran; Sabarinathan, Murugan; Dhanush, Manokaran; Kalaiyarasan, Venkatachalam; Gopikrishnan, Duraisamy; Palanisamy , Mahakrishnan; Selvaraju, Mani (The Indian Journal of Animal Reproduction, 2024)
The estimation of acrosomal integrity is crucial for predicting the fertility of spermatozoa. The semen quality analysis demands assessment techniques to be reliable, quick and easy to perform for routine application in semen station. A study was conducted to assess the acrosomal integrity of Kangayam cattle and Salem Black goat using Giemsa stain and modified Trypan Blue-Giemsa stain. For this procedure, 70 numbers of frozen semen straws of Kangayam bull and Salem Black bucks were stained. The staining quality and acrosomal integrity were assessed at the interval of 3, 5 and 24 hours interval up to 5 days, and evaluated as acrosomal intact and non-intact spermatozoa. In Kangayam bull semen, the quality of the staining was good and better in trypan blue – Giemsa stain than Giemsa alone but for Salem Black buck semen Giemsa showed better staining quality than trypan blue – Giemsa combination. However, the working solution of Giemsa once prepared can be used for 4 days but the trypan blue-Giemsa stain can be used for only 24 hours once prepared. Hence, stain is required to be prepared on daily basis for routine semen evaluation in semen stations. As a conclusion trypan blue – Giemsa staining method is recommended for better staining of acrosome in bull semen and Giemsa alone in Buck semen.